Commodification and crime: a comparison of literary representations of New York and Shanghai since the 1980s - Cai, Jiaying (2012)
This dissertation provides a close textual analysis of a selective number of New York and Shanghai novels published since the 1980s. It focuses on the formal and thematic features of these novels through comparative analyses of the themes of commodification and crime. Part I draws on the work of Jay McInerney, Bret Easton Ellis, Candace Bushnell, Wei Hui and Wang Anyi. It examines how commodification has become not just a feature of global fiction but how writers are drawn to a narrative of excess in their representations of it. Wei Hui's "body writing" shares the same materialistic emphasis as New York "Brat Pack" writing but in their criticism of material excess, their approaches are different. The markets in which these writers and their novels circulate also show how commodification can take control of their reception and lead to different interpretations and misinterpretations. Part II of the dissertation draws on the work of Qiu Xiaolong and Linda Fairstein. Through a close analysis of the representation of time and space, this part argues that both authors' deployment of time and space serves as a strategy to reveal the different social contexts that form the latent causes of individual crimes. By introducing a comparative analysis, this dissertation demonstrates that the shared themes of commodification and crime need to be contextualized within the two cities in order to understand the varied manifestations of the ongoing process of urbanization and its consequences for the literatures and cultures of New York and Shanghai.